DIRECTIONS OF POST-SPORT ADAPTATION OF PROFESSIONAL ATHLETES - Ryskin, Petr; Volovik, Tatiana; Vashlyaeva, Irina (Revista Inclusiones, 2020)
The purpose of the study is to determine the directions of post-sports adaptation of professional athletes in modern Russia. As the theoretical basis of the study, the provisions of institutional theory are used. The research method is a survey of representatives of professional sports who have completed a sports career. The results of the study show that the life plans of professional athletes are focused mainly on retraining in order to change their type of activity, or an attempt to continue a sports career, but in a different status - a trainer, sport manager, a sports official.